Distribution of Water Quality Parameters Using Equation Multiple Linear Regression - Wahyuningsih, Sri; Andriyani, Idah; Soekarno, Siswoyo; Khoirulloh, Deffa (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Mayang River in Jember Regency has a strategic role in fulfilling people's lives and is a source of water for 79 irrigation areas with a total area of 16,471 hectares. Community use of the Mayang River has the potential to provide input of organic material from waste which can reduce river water quality. The aim of this research is to analyze the spatial distribution of water quality parameters, namely TSS, TDS, pH, DO and BOD. This research uses multiple linear regression techniques to determine the value of the distribution or spatial distribution of Mayang River pollution, as well as identifying water quality variables that are correlated in each region. The research results show that water quality parameters that have a strong correlation are pH (r = 0.74), DO (r = 0.72) and TSS (r = 0.65), moderate correlation with BOD parameters (r = 0.48) and low correlation with BOD parameters. TDS parameters (r = 0.25). Based on the analysis results, it is known that water quality parameters are correlated with different activities in each region. The results of this research can be used as a strategy for monitoring water quality in the Mayang River to control the impact of human activities in the surrounding area. Keywords: Multiple Linear Regression, Spatial Distribution, Water Quality.